ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK PADA MATERI TRANSLASI DI KELAS XI SMA NEGERI 2 KEPULAUAN TANIMBAR - Samaran, Mariana; Ratuanik, Mesak; Kewilaa, Debby M (Sora Journal of Mathematics Education, 2024)
This research aims to analyze students' mathematical representation abilities in translation material using the Indonesian Realistic Mathematics Education Approach in class XI, SMA Negeri 2, Tanimbar Islands. This research was carried out at SMA Negeri 2 in the in the Tanimbar Islands. In this research, a qualitative approach was used. This type of research is research that describes data in the form of words and describes phenomena or facts obtained in the research. The data collection techniques used were research documentation, written tests, and interviews. The data analysis techniques used are data collection, data reduction, data presentation, and data verification or drawing conclusions. The results of research on analyzing students' mathematical representation abilities using a realistic mathematics education approach show that students are able to represent mathematics in visual form by solving problems given by using visual representation indicators correctly, both in the form of tables and graphs, as well as the problem-solving process. Once completed, students are able to represent mathematical symbols by solving the problems given by using mathematical symbol representation indicators according to the concept of translation correctly. Likewise, the problem-solving process is resolved, and students are able to represent written text by simply determining the known information using written text indicators, but in the solving process, they are not able to complete it to get the final result.